Relationships between diet quality, food satisfaction and life satisfaction in mother-adolescent dyads - Berta Schnettler; Edgardo Miranda-Zapata; Ligia Orellana; German Lobos; María del Carmen Lapo; Cristian Adasme-Berrios; Klaus G. Grunert (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
This study examined the relationships between diet quality, satisfaction with food-related life and life satisfaction in mother-adolescent dyads. The sample consisted of 470 mother-adolescent dyads in Temuco, Chile. Mothers and adolescents responded to the Adapted Healthy Eating Index, Satisfaction with Life Scale, and the Satisfaction with Food-related Life scale. Data was analyzed using the Actor-Partner Interdependence Model (APIM) and Structural Equation Modelling (SEM). Diet quality was associated with satisfaction with food-related life, which related to life satisfaction in mothers and adolescents. We did not find direct relationships between diet quality and life satisfaction for either dyad member. Adolescents' diet quality negatively affected their mothers' satisfaction with food-related life; adolescents' food-related life was positively associated with their mothers' life satisfaction. The mothers' satisfaction with food-related life played a mediating role between their own diet quality and life satisfaction. Mothers and their adolescent children affect one another in their dietary patterns and life satisfaction. Child-to-mother influences on food-related experiences show that adolescents' satisfaction with food-related life improves their own and their mothers' life satisfaction. Interventions to promote healthy eating habits must be addressed to both mothers and their adolescent children.